The educational experiences of the deaf adolescents attending a school for the deaf in Gauteng. - Van Zyl, Nicola (My University, 2012)
This study aimed to describe the educational experiences of deaf adolescent learners attending a school for the deaf in South Africa. The specific objectives of the current study included: (a) obtaining a detailed description of the educational experiences of deaf adolescent learners; (b) establishing with which rhetoric (medical vs. cultural) the deaf adolescents could best identify; (c) establishing the potential influence on individual identity development of the established affiliations with the opposing models of deafness. Ten deaf adolescents ranging between 14 and 16 years, attending a single school for the deaf were selected as participants for the current study. A basic research design and a qualitative approach, embedded within the theory of social constructivism were employed. Two pilot studies were conducted in order to establish the feasibility of the current study. Thereafter, interviews as per the ‘interview guide approach’ were administered. Field observations within the school context and file reviews were also conducted. Thematic content analysis was employed and the identified themes were described qualitatively. Results revealed the emergence of three themes. Within these themes, the adolescents’ experiences included: limited SASL role models both at home and at school, negative educational encounters as well as positivity and hope for the future. Experiences characteristic of the medical model and socio-cultural model of deafness were reported and factors affecting these affiliations were described. The researcher concluded that a level of affiliation with both the medical and the sociocultural models of deafness existed for the participants. The impact of these affiliations on identity construction was explored and a model of identity development, the multiculturalexperience model, was proposed. The education of deaf individuals in South Africa shows room for significant growth. By adjusting government education policies for deaf education as well as supporting the goals of early intervention, deaf learners can reach their full potential regardless of the mode of communication favoured.
Keywords: Deaf; Hard-of-hearing; Education; Interview; Experience; Identity construction